2014
DOI: 10.1016/j.biocel.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria: A kinase anchoring protein 1, a signaling platform for mitochondrial form and function

Abstract: Mitochondria are best known for their role as cellular power plants, but they also serve as signaling hubs, regulating cellular proliferation, differentiation, and survival. A kinase anchoring protein 1 (AKAP1) is a scaffold protein that recruits protein kinase A (PKA) and other signaling proteins, as well as RNA, to the outer mitochondrial membrane. AKAP1 thereby integrates several second messenger cascades to modulate mitochondrial function and associated physiological and pathophysiological outcomes. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 48 publications
1
85
0
Order By: Relevance
“…It is worth noting that recent studies have shown that the PKA/AKAP1/Drp1 complex also plays a role in mitochondrial function [17,28]. Further studies should be conducted to determine whether these two AKAPs, GSKIP and AKAP1, have competitive, cooperative or distinctive functions and to determine their corresponding locations in Drp1-dependent mitochondrial fission.…”
Section: A Model Of Gskip Gsk3β Pka Rii and Drp1 Interactionmentioning
confidence: 96%
“…It is worth noting that recent studies have shown that the PKA/AKAP1/Drp1 complex also plays a role in mitochondrial function [17,28]. Further studies should be conducted to determine whether these two AKAPs, GSKIP and AKAP1, have competitive, cooperative or distinctive functions and to determine their corresponding locations in Drp1-dependent mitochondrial fission.…”
Section: A Model Of Gskip Gsk3β Pka Rii and Drp1 Interactionmentioning
confidence: 96%
“…Several alternative splice forms of AKAPs exist in tissues of the heart, liver, kidney, brain, and skeletal muscle (11). Dependent on the specific N-terminal amino acids present in the spliced variants of AKAPs, these proteins cannot only scaffold different macromolecules, but also attain the ability to transfer these macromolecules to various subcellular compartments including the nucleus, plasma membrane, golgi apparatus, and endoplasmic reticulum (ER) (7,10).…”
Section: Localization Of Akap121 Isoforms and Their Functionsmentioning
confidence: 99%
“…A fourfold reduction of AKAP149 gene expression was detected in adipose tissue of obese patients [95--97]. AKAP1 localizes predominantly type II PKA and other interaction partners to the outer mitochondrial membrane (reviewed in [98]). AKAP1 associates with mRNAs, e.g.…”
Section: Akaps In Glucose Homeostasis and Obesitymentioning
confidence: 99%